The link between BDNF and platelets in neurological disorders - Nezha Bouhaddou; Meryem Mabrouk; Farah Atifi; Abdelhakim Bouyahya; Younes Zaid (Heliyon)
Platelets are considered one of the most important reservoirs not only of growth factors, but also of neurotrophic factors that could contribute to the repair of vascular lesions and the prevention of neurological deterioration. Among these factors, Brain-Derived Neurotrophic Factor (BDNF) - a protein belonging to the neurotrophin family - is widely expressed both in the hippocampus and in platelets. Platelets constitute an important reservoir of BDNF; however, little is known about the factors modulating its release into the circulation and whether anti-platelet drugs affect this secretion. In this review, we have discussed the link between BDNF and platelets and their role in neurological disorders.